Reliability of the Laboratory Risk Indicator in Necrotising Fasciitis (LRINEC) score. Issue 5 (October 2019) - Abdullah, Muhammad; McWilliams, Billy; Khan, Saad U.
Abstract: Background: The LRINEC score was introduced in 2004 but it has not yet been incorporated as a reliable diagnostic tool in the management of Necrotising Fasciitis. NF is uncommon and proportionately the evidence is limited, but the contradictory literature has resulted in varying individual concepts and clinical practices. This article is aimed to evaluate the reliability of the LRINEC score and determine its effectiveness based on the current available evidence. Methods: Eighteen clinical studies published during 2004–2018 were identified after an extended literature search and critically appraised to determine the validity, reliability and applicability of the individual pieces of evidence. The recommendations for practice were formulated after summative analysis of the evidence. Results: The systemic review and observational studies report the LRINEC score has a variable range of sensitivity (43.2–80%), positive predictive value (57–64%) and negative predictive value (42–86%) which is lower than the initial results by Wong et al. (2004). The LRINEC score ≥6 correlates well with diagnosis of NF but 7.1 was found to be statistically significant. Higher LRINEC score correlates with higher SOFA score, prolonged ICU and hospital stay, and mortality. It is not sensitive in immunocompromised patients. Conclusions: There is Level 3 evidence that LRINEC score is a reliable tool which can aid the clinical diagnosis of NF. It can stratify the high-risk patients and predict outcome; however, it should be correlated with the clinical assessment and radiological diagnostic modalities should be simultaneously used when doubt exists (grade C). Highlights: Diagnosis of NF is difficult in early stages. Evidence shows LRINEC score as a useful adjunct to clinical assessment. Prospective research is required to further evaluate its diagnostic accuracy.